Cohort working life tables for older Canadians - Frank T. Denton; Christine H. Feaver; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2009)
We construct cohort working life tables for Canadian men and women aged 50 and older and, for comparison, corresponding period tables. The tables are derived using annual single age time series of participation rates for 1976-2006 from the master files of the Statistics Canada Labour Force Survey. The cohort calculations are based on stochastic projections of mortality coupled with alternative assumptions about future participation rates. Separate tables are provided for the years 1976, 1991, and 2006, thus spanning a period of substantial gains in life expectancy and strong upward trends in female participation.
Keywords: J10; J26; 330; Cohort working life tables; Arbeitswelt; Ältere Arbeitskräfte; Altersgrenze; Kanada